(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Tooth restoration one of the most common procedures in dental practice. The replacement of the entire restoration leads to loss of tooth structure and increase risk of pulp injury; replacement is also time consuming and costly. According to the minimally invasive approach when minimal defects, repair is the better choice than the total replacement of the restoration. This study aims to evaluate repair rating versus replacement treatment procedure for defective composite fillings among Iraqi dentists. Material and methodology: A questionnaire survey were designed and distributed to 184 post-graduate dentists in Iraq. The inquiry pertained general information; including their clinical experience in years, their preference in terms of direct composite restoration, repair or replacement of old restorations, whether they taught the indications for repair, and the selection type of composite for repair. Result of 200 questioner’s disrepute, 184 questionnaires were completed and collected. The data revealed that the respondents with 1-5, 6-15 and16-25 years of experience were 62 (33.7%), 75 (40.8%), and 47(25.5%) of total respondents, respectively. The total 174 dentists (94.6%) prefer using tooth-colored restorations and 10 (5.4%) dislike this approach. Result clearly indicate that most of the dentists choose replacement for any fractured or discolored restorations. The data showed that 59.2% of dentist are not familiar with repair, and 40.8% dentists are familiar. The result revealed that 82.1% the dentists were not trained on repair during their undergraduate study. Generally, they had no ideal standard to replace or repair depending on their clinical experience. Therefore, clear criteria and guidelines for replacing and repairing should be developed and followed in post-graduate courses.